Associations between different weight‐related anthropometric traits and lifestyle factors in Norwegian children and adolescents: A case for measuring skinfolds. Issue 6 (17th October 2018) - Kristiansen, Hege; Eide, Geir Egil; Brannsether, Bente; Roelants, Mathieu; Bjerknes, Robert; Júlíusson, Pétur B.
Abstract: Objectives: The purpose of this study was to investigate the association between weight‐related anthropometric measures and children's eating habits, physical activity and sedentary lifestyle at a population level. Methods: Data from the Bergen Growth Study were used to study the association of z‐scores of waist circumference (WC), weight‐to‐height ratio (WHtR), subscapularis (SSF) and triceps (TSF) skinfolds and BMI, with lifestyle factors in 3063 Norwegian children (1543 boys) aged 4‐15 years, using linear regression analysis. Each sex was analyzed separately. Results: In a fully adjusted model with additional correction for BMI z‐scores, the consumption of vegetables was associated with higher WC (b = 0.03) and TSF (b = 0.05) z‐scores in girls. Sedentary behavior was not associated with any of the anthropometric measures. Physical activity was negatively associated with SSF (b = −0.07) and TSF (b = −0.07) z‐scores in boys, while a significant negative association was observed with WC (b = −0.02), WHtR (b = −0.03), SSF (b = −0.04) and TSF (b = −0.06) in girls. Conclusion: Physical activity was negatively associated with skinfolds in both sexes. The BMI was not related to the level of physical activity, and should be complemented with direct measures of fat tissue, like skinfolds, when studying the effect of physical activity on body composition in children.